SUMATIVE ANALYSIS BASED ON LEVEL OF DIFFICULTY BASED ON HOTS ITEMS IN INDONESIAN LANGUAGE SUBJECT CLASS VII MTs AL KHOIRIYAH - Al Ayubi, Adib Shofi Silahudin; Lestari, Laila Tri; Ihsan, Bisarul (EDU-KATA, 2024)
This research will discuss studies related to learning evaluation, more precisely it will analyze HOTS-based summative multiple choice questions in grade 7 at MTs Al Khoiriyah Sidodowo school. This research uses a qualitative descriptive methodology, with 3 techniques, namely observation, documentation and interviews. The results of the research showed that there were 5 questions in the LOTS category consisting of very easy and easy category questions. There are 17 questions in the MOTS category, consisting of medium category questions and 3 questions in the HOTS category.